Three Ur-Dynasty Documents - Sollberger, Edmond
I. Derby Education Committee, Museum Service, inv. no. 29; II. Royal Scottish Museum, Edinburgh, Dept. of Art and Archaeology, inv. no. 1907-690-44; III. Private Possession, London.